High School Students in Architecture and Construction Management University Summer Camp Program - Wao, Joel Ochieng; Huie Dixon, Emile; Hunt III, Rogers; Rodgers, Charner (International Journal of Scientific Research and Management (IJSRM), 2022)
Recruiting high school students to join undergraduate educational programs can be challenging for many universities. Alleviating the challenges may require approaches that attract and retain interested quality students. Some programs go through rigorous screening processes requiring students to take, pass and submit their Scholastic Aptitude Test (SAT) scores, high school Grade Point Average (GPA) scores, and/or even interviewing applicants to evaluate their capabilities before admission. Others have extension or specific programs that invite potential applicants to gain theoretical and practical aspects of certain educational programs thereby aiding students in making informed decisions before applying. This latter approach may prove better as it provides the platform for admission team to interact with students beforehand. Thus, an educational summer camp program was conducted targeting high school students who would be interested in pursuing Architecture and/or Construction Management (CM) undergraduate education. Survey questionnaire was administered to students at the beginning, middle and end of the program. The aim was to investigate the factors that made them choose the program, their prior knowledge of the two disciplines and how their interests in the disciplines changed over time after exposure to the summer program. All students were in the same environment from the beginning to the end where they had a chance to choose architecture or CM. Data were gathered and analyzed with MS Excel owing to the non-complexity of the data that did not require sophisticated analysis software. Results showed greater interest of students with clear understanding and distinction of architecture and CM, and demonstrating steadfast attitude to join the disciplines after high school. The research provided potential factors that recruiters and students may consider for undergraduate admissions as well as importance of active learning as a strategy for efficient educational mastery and excellence.